Chapter Gli archivi delle famiglie signorili trentine - Cagol, Franco (Reti Medievali E-Book, 2023)
The historical vicissitudes of the stately Trentino and Tyrolean archives are extremely complex. Archives have long been preserved in castles and aristocratic homes (and in some cases still are); until the end of the 19th century they underwent manipulations, transfers, splits linked to the functioning of the aristocratic society of the Habsburg empire, with the transfer of funds also to distant territories (Czech Republic, Bavaria, etc.). Only recently have the provincial archives of Bolzano and Trento become the most significant place for preserving the memory of the Trentino aristocracy.